Transformation of Waqf Management in The Digital Era: A Meta Synthesis Study - Ade Nur Rohim; Prima Dwi Priyatno; Lili Puspita Sari (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Purpose: This study aims to synthesize several research results that have been carried out related to the digitization of waqf management by various waqf nazhir.Design/Method/Approach : A qualitative approach was used in this study with a meta-synthetic method of 20 scientific journal articles that studied digitalization in waqf socialization and waqf collection.Findings: The results of this study indicate that the Indonesian Waqf Board as the locomotive of national waqf management seeks to build a digital waqf ecosystem nationally by going through several stages. Starting from BWI's internal digitization, digitizing nazhir waqf and integrating waqf data. In addition, the process of accelerating the strengthening of the digital ecosystem through innovation in digital waqf management is also carried out. In the socialization process, waqf is introduced to the public through the use of various digital platforms, such as websites and social media. The socialization covers the basic concept of waqf to an invitation to waqf to the community.Originality/Values: The process of collecting waqf has also been transformed by utilizing various digital payment applications (e-payments) that offer convenience and flexibility for waqf to make waqf.